Pair production of Dirac particles in a d + 1-dimensional noncommutative space–time - OUSMANE SAMARY, DINE; N'DOLO, EMANONFI ELIAS; HOUNKONNOU, MAHOUTON NORBERT (My University, 2014)
Thiswork addresses the computation of the probability of fermionic particle pair production in (d + 1)- dimensional noncommutative Moyal space. Using Seiberg– Witten maps, which establish relations between noncommutative and commutative field variables, up to the first order in the noncommutative parameter θ, we derive the probability density of vacuum–vacuum pair production of Dirac particles. The cases of constant electromagnetic, alternating time-dependent, and space-dependent electric fields are considered and discussed.
Keywords: Pair Production; Dirac Field; Noncommutative field theory